Hypnotic-based intervention for people with non-communicable diseases : A scoping review - Baskoro, Danang Setyo Budi; Yuniarti, Kwartarini Wahyu; Lufityanto, Galang (Universitas Muhammadiyah Malang, 2024)
This scoping study aimed to explore the use of hypnotic-based interventions for individuals with Non-Communicable Diseases (NCDs). Four research questions were addressed: the types of hypnosis-based interventions, the types of NCDs studied, the targeted outcomes, and the evidence of effectiveness. Using Arksey and O'Malley's framework, a systematic search of databases (Cochrane Library, Google Scholar, Scopus, PubMed) was conducted from March to April 2021. Studies published in English between 2001 and 2021, employing Randomized Controlled Trials (RCTs), were included. Out of 6,382 unique records, 11 primary studies met the inclusion criteria, encompassing 589 participants across four NCD subgroups: diabetes, chronic respiratory diseases, cancer, and cardiovascular diseases. Five types of hypnotic interventions were identified: mindfulness, relaxation, self-hypnosis, hypnotherapy, and cognitive behavior therapy plus hypnosis. The outcomes assessed included pain, fatigue, anxiety, sleep quality, dyspnoea, emotion, panic, and quality of life. While the results suggest that hypnotic-based interventions hold promise as supportive therapy for NCD patients, especially in addressing psychological symptoms, the evidence remains inconclusive. Further research is needed to establish the overall effectiveness of hypnosis in this context. Nonetheless, these findings highlight the potential of hypnosis to complement medical treatments for NCDs.